2015
DOI: 10.1007/s00029-015-0188-8
|View full text |Cite
|
Sign up to set email alerts
|

Quivers with potentials associated to triangulated surfaces, part IV: removing boundary assumptions

Abstract: We prove that the quivers with potentials associated with triangulations of surfaces with marked points, and possibly empty boundary, are non-degenerate, provided the underlying surface with marked points is not a closed sphere with exactly five punctures. This is done by explicitly defining the QPs that correspond to tagged triangulations and proving that whenever two tagged triangulations are related to a flip, their associated QPs are related to the corresponding QP-mutation. As a byproduct, for (arbitraril… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 16 publications
0
61
0
Order By: Relevance
“…In [22] it is further shown that the corresponding quivers with potential are also related by a sequence of mutations, and it follows then from [17] that the corresponding categories D f d (Γ) are equivalent as triangulated categories, likewise for C (Γ). We therefore write simply D(S) = D f d (Γ) and C (S) = C (Γ) in this case.…”
Section: Preliminariesmentioning
confidence: 99%
“…In [22] it is further shown that the corresponding quivers with potential are also related by a sequence of mutations, and it follows then from [17] that the corresponding categories D f d (Γ) are equivalent as triangulated categories, likewise for C (Γ). We therefore write simply D(S) = D f d (Γ) and C (S) = C (Γ) in this case.…”
Section: Preliminariesmentioning
confidence: 99%
“…Now choose any puncture q. A minor modification of the proof of [LF3,Proposition 11.2] proves that S(τ, x) is right equivalent to S(τ, w), where w = (w p ) p∈P is defined by w q = p∈P x p , and w p = 1 for p = q.…”
Section: M| ≥mentioning
confidence: 99%
“…Given the definition of the QPs associated to tagged triangulations (cf. [LF3,Definition 3.2]), this implies that both S(τ, x) and S(σ, x) are non-degenerate (recall that τ and σ have been assumed to be tagged triangulations).…”
Section: M| ≥mentioning
confidence: 99%
See 1 more Smart Citation
“…Still, in particular its Jacobian algebras are not well understood, yet. Consider the two non-degenerate potentials W := γ 1 β 1 α 1 + γ 2 β 2 α 2 W ′ := γ 1 β 1 α 1 + γ 2 β 2 α 2 − γ 2 β 1 α 2 γ 1 β 2 α 1 yielding one infinite dimensional Jacobian algebra Λ = P(Q, W ) [DWZ1,Example 8.6] and one finite-dimensional Jacobian algebra Λ ′ = P(Q, W ′ ) [La,Example 8.2]. Recently Geuenich [G] proved that there are infinitely many non-degenerate potentials for Q up to right equivalence.…”
Section: Introductionmentioning
confidence: 99%